Speech Portrait of Slovak Student - Elena N. Strelchuk; Gmira Tomash (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2018)
The article offers a description of the speech portrait of a Slovak student who learns Russian. The main aspects of the Russian language, types of speech activity, situations and spheres of communication that are relevant in the process of studying Russian by Slovaks are considered. The factors influencing the formation of the speech portrait of a Slovak student are determined.